The All-Cause Mortality and a Screening Tool to Determine High-Risk Patients among Prevalent Type 2 Diabetes Mellitus Patients - Mohamad Adam Bujang; Pei Xuan Kuan; Xun Ting Tiong; Fatin Ellisya Saperi; Mastura Ismail; Feisul Idzwan Mustafa; Abd Muneer Abd Hamid (Journal of Diabetes Research)
Aims. This study aims to determine the all-cause mortality and the associated risk factors for all-cause mortality among the prevalent type 2 diabetes mellitus (T2DM) patients within five years’ period and to develop a screening tool to determine high-risk patients. Methods. This is a cohort study of T2DM patients in the national diabetes registry, Malaysia. Patients’ particulars were derived from the database between 1st January 2009 and 31st December 2009. Their records were matched with the national death record at the end of year 2013 to determine the status after five years. The factors associated with mortality were investigated, and a prognostic model was developed based on logistic regression model. Results. There were 69,555 records analyzed. The mortality rate was 1.4 persons per 100 person-years. The major cause of death were diseases of the circulatory system (28.4%), infectious and parasitic diseases (19.7%), and respiratory system (16.0%). The risk factors of mortality within five years were age group (p<0.001), body mass index category (p<0.001), duration of diabetes (p<0.001), retinopathy (p=0.001), ischaemic heart disease (p<0.001), cerebrovascular (p=0.007), nephropathy (p=0.001), and foot problem (p=0.001). The sensitivity and specificity of the proposed model was fairly strong with 70.2% and 61.3%, respectively. Conclusions. The elderly and underweight T2DM patients with complications have higher risk for mortality within five years. The model has moderate accuracy; the prognostic model can be used as a screening tool to classify T2DM patients who are at higher risk for mortality within five years.